Adsorption of benzothiophene sulfone over clay mineral adsorbents in the frame of oxidative desulfurization - Choi, Angelo Earvin Sy (Animo Repository, 2017)
The adsorption of benzothiophene sulfone (BTO) from model fuel oil was investigated using three different clay mineral adsorbents. The adsorption characteristics of clay mineral adsorbents such as activated clay, bentonite and kaolinite were evaluated using Fourier transform infrared spectroscopy and Brunauer, Emmett and Teller surface area analyzer. A batch process was conducted to determine the adsorption performances at varying contact time, reaction temperature and initial concentration. Increasing adsorption capacities followed the order of kaolinite < bentonite < activated clay. The equilibrium isotherms using Langmuir and Freundlich models yielded a good fit (R2 > 0.98) indicating a monolayer and heterogeneous adsorption. A second order reaction kinetic model showed high suitability (R2 > 0.97) based on the experimental data. Results showed that adsorption follows a two-step process: (1) fast adsorption rate for the first two hours and (2) markedly slow adsorption rate until equilibrium. The clay minerals have different functional groups present in its surface which determines the essential adsorption characteristics. The thermodynamic parameters for BTO adsorption onto clay mineral adsorbents indicated an endothermic reaction. Activated clay and kaolinite were spontaneous and non-spontaneous, respectively, while bentonite was found to be only non-spontaneous at 25 °C. In comparison with conventional adsorbents, activated clay was found to be superior in the application of sulfone adsorption in fuel oil. © 2017